Haavikko’s technique for dental age estimation: Brazilian application and technique variation at the age of 10 years - Isabella de Lima Silva; Brendha Ogando; Rosemary Sadami Arai Shinkai; Cláudio Costa; Hrvoje Brkić; Edgard Michel-Crosato; Maria Gabriela Haye Biazevic (Egyptian Journal of Forensic Sciences)
Abstract Background Estimating the age of children and adolescents is a constant challenge for Forensic Anthropology and Legal Dentistry. The relevance of age estimation in living individuals is related to its contribution in civil and criminal contexts, particularly for age determination in adoption processes, criminal responsibility, pedophilia, lack of valid identification documents, as well as its application in migration and asylum requests in foreign countries. The objectives of the study were: to estimate the age of a sample of Brazilian children and adolescents using the Haavikko’s technique; and to verify the feasibility of using a technique variation for estimating the age of individuals at 10 years, which is the cutoff point at the original technique. The sample consisted of 399 panoramic radiographs, which were distributed according to sex and age: approximately 50 panoramic radiographs for each age (6 to 14 years), with 25 males and 25 females per age. The data were analyzed with the Python programming language, using the packages Matplotlib, Seaborn, Scipy.stats, and Numpy. Results The results showed strong intra-examiner agreement and similarity between actual and estimated age, with no measurement error exceeding 2.5 months. It is possible to estimate the age of individuals using the variation of the Haavikko’s technique, since the mean error was low (1.02 ± 0.62 and 0.89 ± 0.62, respectively). Conclusions We conclude that the technique is replicable and can be applied with a low error rate in the Brazilian population.